2017
DOI: 10.3390/catal7030075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Nano-Sized Silica Sols as Supports on the Structure and Properties of Cu/SiO2 for Hydrogenation of Dimethyl Oxalate

Abstract: Cu/x-SiO 2 catalysts with 4, 10, and 20 nm silica sols as supports was produced by ammonia evaporation method and characterized. Different nano-sized silica sols as supports significantly affected the structure and catalytic properties of the copper catalysts for ethylene glycol synthesis from dimethyl oxalate. Compared with Cu/20-SiO 2 and Cu/4-SiO 2 catalysts, the catalytic performance and stability of Cu/10-SiO 2 catalyst were greatly enhanced. The Cu/10-SiO 2 catalyst showed 99.9% conversion with 94% EG se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…However, its potential in industrial applications was limited by its poor stability (<100 h), which was caused by the aggregation of Cu NPs, carbon deposition, and the loss of silica via the formation of tetramethoxysilane with methanol. , To enhance the long-term properties of Cu-SiO 2 based catalysts, several methods have been introduced in the literature. Using nanosized silica sols to regulate Cu NP size and dispersion. For instance, silica sols 10 nm in size have been demonstrated to be capable of restraining the migration and growth of copper species Confining Cu NPs in phyllosilicate nanotubes by a hydrothermal method. ,, Using ordered mesoporous SiO 2 (OMS) as the support for Cu NPs.…”
Section: Recent Progress In Catalyst Design For Dmo Hydrogenationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, its potential in industrial applications was limited by its poor stability (<100 h), which was caused by the aggregation of Cu NPs, carbon deposition, and the loss of silica via the formation of tetramethoxysilane with methanol. , To enhance the long-term properties of Cu-SiO 2 based catalysts, several methods have been introduced in the literature. Using nanosized silica sols to regulate Cu NP size and dispersion. For instance, silica sols 10 nm in size have been demonstrated to be capable of restraining the migration and growth of copper species Confining Cu NPs in phyllosilicate nanotubes by a hydrothermal method. ,, Using ordered mesoporous SiO 2 (OMS) as the support for Cu NPs.…”
Section: Recent Progress In Catalyst Design For Dmo Hydrogenationmentioning
confidence: 99%
“…Using nanosized silica sols to regulate Cu NP size and dispersion. For instance, silica sols 10 nm in size have been demonstrated to be capable of restraining the migration and growth of copper species …”
Section: Recent Progress In Catalyst Design For Dmo Hydrogenationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that Cu has a good hydrogenation ability of C-O bonds, while it does not favor the hydrogenolysis of C-C bonds [13,14], thus showing good catalytic activity in the hydrodeoxygenation of FFA. Copper-chromium catalysts are commonly used in the hydrogenation of aldehydes, ketones or esters [15][16][17][18][19]. Adkins et al [20] found that the earliest copper-chromium catalyst, Cu 2 Cr 2 O 5 , could be utilized in catalytic hydrogenation.…”
Section: Introductionmentioning
confidence: 99%